Building a Salesforce-powered front office : a quick-start guide - Chowdhury, Rashed A. (Apress, 2021)
Harness the power of Salesforce to manage and grow your business. This book shows you how to use the Salesforce CRM tool to consolidate consumer data into a single place to gain better insight into your business and more easily manage data. Data (such as email, spreadsheets, databases) is generated through the front office or face of your business, where your company interacts with customers and revenue is generated. In a hotel, for instance, the front office is the lobby where guests are greeted, their problems are handled, and room payments are made. Another example is a coffee shop, where the front office is an employee taking a customer's order or serving a drink. Salespeople connect to customers by selling your companys goods or services. Marketing team members connect with them through advertising and promotional activities. Service and support staff assist customers with problems and provide help with products. This book introduces the many ways Salesforce-based innovations are transforming the technology landscape and the strategies that may be used for designing and launching a digital front office. The book examines how organizations can launch and grow digital solutions and strategies for the governance of the platform and provides an overview of digital transformation across industries. You will: Understand basic Salesforce concepts, including the digital front office process tower, lead to cash journey, core CRM functions, best practices, and more Review data management concepts, integrated sales, customer service, marketing operations, and proposal and business development needs in a systematic way Use frameworks to build a business architecture and multi-year technology roadmap Get familiar with Salesforce business processes and concepts such as account, contact, lead, and opportunity management; marketing campaigns; master data management (MDM); and lead scoring, grading, and activity management across the front office Define and develop digital marketing challenges and strategy (people, process, brand, messaging, and ROI), measure campaign data, and create an end-to-end campaign in Salesforce.